Reducing Downtime on Injection Molding Machines Using the Overall Equipment Effectiveness (OEE) Method at PT Mah Sing Indonesia - David Rakes; Hasyrani Windyatri; Suhendra Suhendra (Journal of Social Science, 2024)
In today's increasingly globalized industrial competition and rapid technological advancements, manufacturing companies strive to improve the quality and quantity of their products. However, intensive use and occasional overloading of machines can lead to decreased performance, shortened lifespan, and component failures. Machine failures not only cause costly downtime but also pose safety risks to workers. This study focuses on PT. Mah Sing Indonesia's efforts to optimize the injection molding process by addressing machine downtime through effective preventive maintenance strategies and comprehensive management approaches. Data collected over the course of 2023 highlights the application of Overall Equipment Effectiveness (OEE) metrics to evaluate machine performance and identify key areas for improvement. The findings underscore the significance of integrating human resources, technology, management practices, and environmental factors to enhance operational efficiency and productivity in injection molding processes.